DETERMINANTS OF INSTABILITY IN RICE PRODUCTION: EMPIRICAL EVIDENCE FROM UTTAR PRADESH - SHOAIB ANSARI*, SAGHIR AHMAD ANSARI AND ALFISHAN REHMAT (The Journal of Research ANGRAU, 2022)
This research examined the determinants of the instability in rice production, which enhancesthe total rice productivity in Uttar Pradesh. The study analysed the relations among variables usedfor the analysis from 1991 to2019.The application of the Auto Regressive Distributed Lag technique(ARDL )was used to approximate various determinants. The area under net irrigation, un-irrigation,and rainfall positively affect rice production. In contrast,un-irrigation and annual rainfall showed apositive but statistically insignificant impact on rice production in the long run. While in the short run,all determinants had a negative and significant effect on total rice production convergence towardsin-equilibrium, shown by the error correction term - 0.42.